Microstructure evolution of TC4 powder by spark plasma sintering after hot deformation - Yan Jiangpeng; Zhang Zhimin; Xu Jian; Wu Yaojin; Zhao Xi; Xue Yong; Liu Haijun (High Temperature Materials and Processes, 2020)
The cylindrical samples of TC4 titanium alloy prepared by spark plasma sintering (SPS) were compressed with hot deformation of 70% on the thermosimulation machine of Gleeble-1500. The temperature of the processes ranged from 850°C to 1,050°C, and the strain rates varied between 0.001 and 5 s−1. The relative density of the sintered and compressed samples was measured by the Archimedes principle. During hot deformation, the microstructure of the sample was observed. The results show that the average relative density of the samples was 90.2% after SPS. And the relative density was about 98% after the hot deformation of 70%. Under high temperature (>950°C), the sensitivity of flow stress to temperature was reduced. At low strain rate (0.001 s−1), the increase in the deformation temperature promoted the growth of dynamic recrystallization (DRX). At the same temperature, the increase in strain rate slowed down the growth of DRX grains. And the variation tendency was shown from the basket-weave structure to the Widmanstätten structure at a low strain rate (<0.1 s−1), with increase in the strain rate.